Problems and Potential of Swamp Ecosystems to Support Economic Development: Case Study in Tapin Regency - Ahmad Baparki (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This study explores the challenges and economic potential of swamp ecosystems in supporting sustainable regional development in Tapin Regency, South Kalimantan. Employing a descriptive-exploratory qualitative approach, data were obtained through field observations, semi-structured interviews with community members, government officials, and stakeholders, as well as analysis of secondary documents. The research focused on two sub-districts—South Candi Laras and North Candi Laras—which are characterized by extensive swamp areas and active community utilization. The results indicate that the swamp ecosystem in the region plays a vital role in supporting local livelihoods across four main sectors: fisheries, swamp-based agriculture, livestock, and tourism. Inland fisheries, including pond and cage cultivation, show significant annual productivity, especially in North Candi Laras. Agriculture, dominated by seasonal rice farming, contributes substantially to regional food security. Livestock activities, particularly duck and buffalo farming, demonstrate compatibility with swamp conditions and offer opportunities for expansion. Tourism, although still underdeveloped, holds strong potential for nature-based and river tourism. However, various constraints impede optimal development, including poor infrastructure, limited access to markets, environmental degradation, and low community capacity in resource governance. The study highlights that community empowerment, local participation, and context-sensitive policy interventions are critical for enhancing the sustainable management of swamp resources. Furthermore, integrating ecological conservation with economic utilization is essential to transform swamp ecosystems into strategic assets for inclusive and resilient development. This research serves as a foundation for further studies on participatory regional planning and ecosystem-based economic strategies in wetland regions.